Academic Senate Minutes 2007-10-11 - Academic Senate:::::::::
Announcements from the Chair. Chair Report. Approval of Agenda. Minutes delayed. Recommendations from Structure and Functions for faculty on committees approved. Special Report: Sponsored Programs Subcommittee end of year recommendations to the CFO & Provost regarding minimum IDC, distribution of IDC & criteria for SSU approval of external grant proposals. Revision to Cheating and Plagiarism Policy approved. 30 minute conversations at the Senate referred to Executive Committee. Resolution: Reaffirmation of University Policy on Non-Discrimination - First Reading.